SIMULATION AND ANALYSIS OF COMPOUND ABRASIVE GRINDING PERFORMANCE OF SPIRAL BEVEL GEARS (MT) - LIU Bin; YAN ChangFeng; WEI LiLin; YANG HaoDong; ZHAO XiaoMan (Jixie qiangdu)
The grinding of spiral bevel gears is a nonlinear and dynamic complex process. It is significant to explore the complex grinding mechanism of spiral bevel gears by simulating the grinding process based on finite element method. A finite element model of composite abrasive grinding was established based on material constitutive equation of Johnson-Cook force-thermal coupling. And the changes in the tooth surface temperature field, grinding force and abrasive wear were compared and analyzed under different grinding speeds, grinding depths and abrasive spacing condition. The simulation results were also verified by the experimental results.The results show that the grinding depth is the most important factor to affect the grinding surface performance. The influence of the compound abrasive grain interference on the tooth surface temperature field and the resulting grinding vibration cannot be ignored. It could provide theoretical guidance for the research and practical processing of grinding surface performance of spiral bevel gears.